Influence of School Principal Transformational Leadership and Work Motivation on the Performance of Banjarbaru Private Junior High School Teacher - Wabibah, Didin Iis Wahyu; Suhaimi, Suhaimi; Ahmad, Karyono Ibnu; Noor, Ihsan (Technium Education and Humanities, 2024)
Internal and external factors influence the low performance of junior high school teachers. Private junior high school (SMP) teachers in Banjarbaru are strongly influenced by transformational leadership, work motivation, and job satisfaction, so improving teacher performance by identifying the problems they face and finding alternative solutions is necessary. The research was conducted to analyze the direct and indirect influence of the principal's transformational leadership and work motivation on performance through job satisfaction of private junior high school teachers in Banjarbaru City. The research design used in this research is descriptive, using a path analysis model (part analysis) to analyze the pattern of influence between variables. The research population was 266 teachers from 14 private junior high schools in Banjarbaru City. Moreover, 160 respondents were taken as research samples using the Probability Simple Random Sampling technique. Data collection uses questionnaire instruments, and data analysis uses descriptive analysis, classical assumption testing, hypothesis testing, and path analysis. The results of the data analysis obtained show that the regression coefficient value of the transformational leadership variable of the principal and teacher performance is 0.396, the variable job satisfaction and teacher performance is 0.365, the variable work motivation and teacher performance is 0.226, the variable principal transformational leadership and job satisfaction is 0.605, the variable work motivation and job satisfaction is 0.290, the variable transformational leadership with performance through job satisfaction is 0.137 and the variable work motivation and performance through job satisfaction is 0.073. The research results show that the level of transformational leadership of school principals, the level of job satisfaction, and the level of teacher performance in junior high schools in the city of Banjarbaru are in the medium category, while the level of work motivation is in the high category. There is a partial direct relationship between the transformational leadership of school principals, work motivation, job satisfaction, and teacher performance in private junior high schools in Banjarbaru. There is an indirect relationship between transformational leadership, work motivation, and performance through job satisfaction in private junior high schools throughout Banjarbaru City, so there is a need to increase the variables of transformational leadership, work motivation, job satisfaction, and teacher performance.